Re-Interpretasi Utopisme â€œPalembang Emas Darussalamâ€ melalui Penyediaan Ruang Terbuka Hijau di Kota Palembang - Raegen Harahap; Siti Anisyah (LPPM Universitas Abdurrab, 2021)
The discourse of ecology-based urban development, by implementing green open space (RTH) based development has long been a global, national and local agenda. However, today there are still many regions, not yet fully able to meet these needs due to various aspects. In this study, it aims to determine how the reality and efforts to provide green open space (RTH) in the city of Palembang to realize a minimum of 30%. This research is also in the form of a research design with descriptive qualitative methods using a case study approach and literature study. The findings obtained in the research are at least in two dimensions, namely (1), that the existential reality of the provision of green open space (RTH) still has many challenges, both from the rate of development, the rate of population growth, and consistency in following up on conversion or transfer offenders. land function; (2), whereas the implementation of the policy is still at the administrative stage and division of field technicians, and there are still many challenges in professionalism and limited support for facilities and infrastructure in the field. Therefore, the city government of Palembang has not fully implemented its policies in fulfilling beautiful urban areas in accordance with the utopianism that was declared in 2012.